Recent Progress in Asymmetric Fluorination and Trifluoromethylation Reactions - Bizet, Vincent; Besset, Tatiana; Ma, Jun-An; Cahard, Dominique (Current Topics in Medicinal Chemistry, 2014)
All domains of society are impacted by fluorine chemistry. In particular, fluorine plays a key role in medicinal, pharmaceutical and agrochemical sciences in which the synthesis and evaluation of molecules featuring one or more fluorine atoms is nowadays routine in every new discovery and development program. Since the beginning of this century, enantiopure fluorinated molecules are at the forefront of innovation of the tremendous achievements in fluorine chemistry. This review introduces the reader to the recent progress in asymmetric installation of one fluorine and a trifluoromethyl group via nucleophilic, electrophilic and radical diastereo- and enantioselective reactions.
Keywords: fluorination